Management Competencies and Their Relationship with Organizational Performance in Small and Medium-Sized Family Businesses - Torres-Rivera, M. Patricia; Pedraza-Melo, Norma Angélica (European Journal of Family Business, 2023)
The objective of the research is to analyze the relationship between managers’ competencies and their businesses performance. The study was approached from the quantitative paradigm, applying a questionnaire to 114 managers of small and medium-sized family businesses, located in the states of Tamaulipas and San Luis Potosí, Mexico. The results shared show, in the context of a family business, the relationship between the study variables, which allows providing knowledge in the family businesses management, which are important economic units in this country, as sources of employment generation. The structural equations technique was applied in the validation of the research hypotheses. It is inferred that only intrategic and personal effectiveness competencies are positively related to organizational performance, with no positive relationship between strategic competencies and organizational performance.